2011
DOI: 10.1002/pros.21499
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of scavenger receptor Class B Type I reduces prostate specific antigen secretion and viability of prostate cancer cells

Abstract: The down-regulation of SR-BI significantly impacts PSA production of prostate cancer cells, as well as the viability of C4-2 cells in the presence and absence of HDL. This may indicate a deficiency in cholesterol availability to the androgen synthesis pathway or may implicate a role for SR-BI in prostate cancer signal transduction pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 63 publications
5
58
0
Order By: Relevance
“…SR-B1 has been implicated in several biological processes such as apoptosis [86,87] entry through TRPC3 channels, leading to dampened cytokine production in response to CpG via TLR9 activation [90]. Disrupting SR-B1 function by genetic or chemical inhibitors may decrease tumor cell malignancy [85,91]. The main mechanisms of action proposed for these therapeutic interventions are the reduced availability of cholesterol and the decreased activation of the PI3K/AKT pathway.…”
mentioning
confidence: 99%
“…SR-B1 has been implicated in several biological processes such as apoptosis [86,87] entry through TRPC3 channels, leading to dampened cytokine production in response to CpG via TLR9 activation [90]. Disrupting SR-B1 function by genetic or chemical inhibitors may decrease tumor cell malignancy [85,91]. The main mechanisms of action proposed for these therapeutic interventions are the reduced availability of cholesterol and the decreased activation of the PI3K/AKT pathway.…”
mentioning
confidence: 99%
“…Further study is therefore required to answer these questions. Several studies have reported the role of SR-BI in diverse solid tumors (7,35,36). For instance, SR-BI was shown to mediate the proliferative and anti-apoptotic features of HDL in MCF-7 breast cancer cells through modulation of cholesterol metabolism (7,8).…”
Section: Sr-bi Expression % (N) -----------------------------------mentioning
confidence: 99%
“…For instance, SR-BI was shown to mediate the proliferative and anti-apoptotic features of HDL in MCF-7 breast cancer cells through modulation of cholesterol metabolism (7,8). Twiddy et al (36) found that SR-BI downregulation caused a significant reduction in prostate-specific antigen production and decreased the viability of prostate cancer cell lines in vitro. Previous studies revealed that SR-BI was associated with more aggressive cancer phenotypes and could serve a tumor-promoting function in breast and prostate cancer (35,37).…”
Section: Sr-bi Expression % (N) -----------------------------------mentioning
confidence: 99%
“…Second, spherical forms of HDL engage the SR-B1 receptor, 3 a receptor found in a variety of cell types, including tumor cells. 65, 66 This may confer inherent target specificity to a class of cells of tremendous interest for therapeutic targeting. Emerging evidence supports the notion that SR-B1 is critical for maintaining cholesterol homeostasis, and that adequate cholesterol uptake is critical for supporting tumor cell growth.…”
Section: Mimics Of Spherical Hdl For Drug Deliverymentioning
confidence: 99%